(untitled) (Journal of Entrepreneurship and Business, 2020)
This study aims to contribute to the extensive literature on transnational entrepreneurship by investigating the relationship between seven categorical independent variables (IVs) and a dichotomous dependent variable within the ASEAN-X group. Specifically, a large dataset from the World Bank, OECD, InBIA, and Southeast Asia Ecosystem Report provided a sample of N = 967. A binary logistic regression model was used to analyze the study questions and hypotheses following the Transnational Entrepreneurship (TE) theory. The modelling results reported that the remittances measured by total transaction costs (WaldX2 = 22.49, df = 5, p < .001), entrepreneurs’ age (WaldX2= 11.78, df = 4, p =.019), entrepreneurs’ education (WaldX2 = 48.33, df = 3, p < .001), and business incubators’ ownership or status (WaldX2 = 14.97, df = 2, p = .001) potentially gauged the success of startup businesses. Future studies should also emphasize the implications of phenomenon-based research in business and society to identify specific theories based on the lived experiences.